Incidence and prevalence of epilepsy in the Republic of North Macedonia: Data from nationwide integrated health care platform. (April 2021) - Babunovska, Marija; Boskovski, Bojan; Kuzmanovski, Igor; Isjanovska, Rozalinda; Kiteva Trencevska, Gordana; Cvetkovska, Emilija
Highlights: Epidemiology of epilepsy was assessed based on nationwide healthcare platform. Incidence and prevalence were higher in males than in females, ratio 1.2:1. Incidence was high in childhood, low in adults, and increased after age of 50 years. Incidence tends to decrease in childhood and increases in group over 50 years of age. Abstract: Purpose: This study aimed to evaluate the incidence and period prevalence of epilepsy in the Republic of North Macedonia, an upper-middle-income country with universal access to healthcare, based on a nationwide healthcare platform (NHP). Methods: NHP contains reports from all inpatient and outpatient medical encounters and procedures, and all electronic medical records are linked together with a unique patient number. We performed the analysis of the data maintained at the Macedonian Ministry of Health, concerning the five years of the study (2014 through 2018). Population and demographic data for each year were obtained from the State Statistical Office. Results: The period prevalence was 6.67 per 1, 000 inhabitants. There were 6383 (46.2%) females and 7435 (53.8%) males; the gender difference was significant: 6.17 per 1, 000 females and 7.16 per 1, 000 males ( p  = 0.0000). Between 2015 and 2018 the median annual incidence of epilepsy was 68 new epilepsy patients per 100, 000, with an upward trend over time. The age-specific incidence was high in childhood and adolescence, was constant (and low) in the adult years, and gradually increased in each successive age group after the age of 50 years. The greatest incidence was found in group 70–79 years of age. The incidence in childhood and adolescence tends to gradually decrease from 2015 to 2018, while it progressively increased in population over 50 years of age, which may explain a rise in overall incidence. We found a statistically significant higher incidence in males than in females, a ratio consistently being 1.2: 1. Conclusion: The data from the study provides accurate findings on the prevalence and incidence of epilepsy in the upper-middle-income Southeastern European country.